Development of Moodle-Based E-Learning on the Website for German Reading Skills A2 - Rina Evianty; Risnovita Sari (Britain International for Academic Research (BIAR) Publisher, 2022)
This study examines the use of Moodle-Based E-Learning on the website for german reading skills A2. The purpose of this study is to define and explain how Moodle-based e-learning can be used in german reading skills A2 because of the low achievement of students in reading skills and not optimal use of the internet in supporting learning success. LMS is one way to develop online learning or e-learning, which is a web-based learning management application that facilitates learners to learn properly in a virtual classroom, a class in a virtual world. The LMS used in this study is a Moodle-based LMS. An analytical descriptive strategy was used as a research method. Therefore, the use of moodle- based e-learning is very suitable for use in learning German, given that currently the world of education cannot be separated from technology and internet networks, besides that there are many educational institutions that have been facilitated by infrastructure in utilizing existing technology. It is also proven that learning with the Moodle as LMS application is more effective than conventional learning in improving students' reading skills. From some of the results and research findings, several suggestions related to this research were put forward, the point of which is that it is time for a change in mindset in responding to the internet as one of the factors that support learning success.